Female and male Character Representation in English Textbooks of Cambodian Secondary Schools: A Sociolinguistic Analysis - Phorn, Chenla; Arsyad, Safnil (JET ADI BUANA, 2022)
Gender representation in the textbook becomes a noticeable topic for many scholars and researchers since it is believed that the representation of female and male influence the learners in many ways. Therefore, the purpose of this study was to find out how female and male characters are represented in listening dialogues from English textbooks in Cambodian secondary schools. The quantitative approach was used in this research study. Moreover, the researcher used descriptive statistical analysis as a tool to investigate the frequencies of women and men characters. The representations appeared in 11 randomly selected conversations in each chapter of the English textbook namely English for Cambodia Grade 7. This method is analyzed based on an adopted model developed by Tahriri & Moradpour (2014) which focuses on three dimensions of gender relation, subject position, and content categories. After analysis, the findings demonstrated that most of the conversations are male-female relations. Three subject positions are shown. Meanwhile, the gender characters countered in all dialogues showed slightly different between women and men. Regarding the content categories, six different categories are found. This study confirms gender bias in textbook that female characters are perceived and presented as being less than their male counterparts.